2016
DOI: 10.3844/ajeassp.2016.323.333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Alumina on Pore Structure and Durability of Class F Fly Ash Self-Compacting Mortar

Abstract: Abstract:In this study the effect of pore structure on the mechanical properties and durability characteristics of Self-Compacting Mortars (SCM) containing nano-Al 2 O 3 (NA) and class F fly ash are investigated. Al 2 O 3 nanoparticles with the maximum size of 15 nm in three different proportions of 1, 3 and 5% of the binder content were utilized to partially replace the cement. The 25% of the cement weight was also replaced by class F fly ash. The pore structure of cement mortars was determined through the Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…erefore, nanoparticles could be considered as an alternative choice to serve as accelerators for cementitious materials under low temperatures. Numerous studies have been conducted on the utilization of nanoparticles, including nano-SiO 2 [12][13][14][15][16][17][18][19][20][21][22], nano-CaCO 3 [17,23,24], nano-Al 2 O 3 [16,20,25], nano-TiO 2 [14,16,[26][27][28][29][30][31][32][33][34][35][36][37][38], nano-Fe 2 O 3 [10,13], and nano-CuO [13,39], in cementitious materials to improve their durability and mechanical properties. Nano-SiO 2 is the most commonly used nanoparticle, while nano-TiO 2 is comparatively favorable for pavement structures in terms of aircleaning property.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, nanoparticles could be considered as an alternative choice to serve as accelerators for cementitious materials under low temperatures. Numerous studies have been conducted on the utilization of nanoparticles, including nano-SiO 2 [12][13][14][15][16][17][18][19][20][21][22], nano-CaCO 3 [17,23,24], nano-Al 2 O 3 [16,20,25], nano-TiO 2 [14,16,[26][27][28][29][30][31][32][33][34][35][36][37][38], nano-Fe 2 O 3 [10,13], and nano-CuO [13,39], in cementitious materials to improve their durability and mechanical properties. Nano-SiO 2 is the most commonly used nanoparticle, while nano-TiO 2 is comparatively favorable for pavement structures in terms of aircleaning property.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mohseni et al [ 8 ] studied the binary and ternary blended mortar containing nanoparticles and fly ash and their results indicated that the inclusion of nanoparticles and FA resulted in high early age strength and long-term strength of mortar. However, most of the previous studies were mainly focused on nano-SiO 2 [ 9 , 10 , 11 ], nano-TiO 2 [ 12 , 13 ] and other metal-containing nanoparticles [ 6 , 14 , 15 , 16 , 17 ]. There are very limited studies on nano-copper oxides (nano-CuO) and their effects on physical and mechanical properties of mortar and concrete [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the four years of the first mission, the ship scanned 150,000 stars, searching for the small falls in light caused by planets that pass in front of them. In 2014, Kepler switched to the second mission called K2, where he still hunts planets but also makes a variety of observations (Wang and Yagi, 2016;Obaiys et al, 2016;Ahmed et al, 2016;Jauhari et al, 2016;Syahrullah and Sinaga, 2016;Shanmugam, 2016;Jaber and Bicker, 2016;Moubarek and Gharsallah, 2016;Amani, 2016;Shruti, 2016;Pérez-de León et al, 2016;Mohseni and Tsavdaridis, 2016;Abu-Lebdeh et al, 2016;Serebrennikov et al, 2016;Budak et al, 2016;Augustine et al, 2016;Jarahi and Seifilaleh, 2016;Nabilou, 2016;You et al, 2016;Zurfi and Zhang, 2016;Rama et al, 2016;Sallami et al, 2016;Huang et al, 2016;Ali et al, 2016;Kamble and Kumar, 2016;Saikia and Karak, 2016;Zeferino et al, 2016;Pravettoni et al, 2016;Bedon and Amadio, 2016;Chen and Xu, 2016;Mavukkandy et al, 2016;Yeargin et al, 2016;Madani and Dababneh, 2016;Alhasanat et al, 2016;Elliott et al, 2016;Suarez et al, 2016;Kuli et al, 2016;…”
Section: The Incredible Quantitymentioning
confidence: 99%